2017
DOI: 10.4028/www.scientific.net/ssp.267.12
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Gels Obtained from Hardwood and Softwood Bark for Reinforcing of Paper

Abstract: For reinforcing of paper, nanoparticle gels from black alder, birch and pine bark were obtained. Non-extracted bark and that extracted in biorefinery were used. For producing nanoparticles, the materials were destructed using the thermocatalytic destruction method and then dispersed in water medium in a ball mill. At a sufficient concentration, gel-like dispersions were obtained, which contained nanoparticles with the size ~300 nm. The effect of nanoparticle gels on the properties of paper sheets was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Nanofibrillated cellulose gel-like dispersion was prepared using mechanical treatment with a high shear force following the previously established method [ 51 ]. NFC fabrication is similar to MCC preparation but involves addition of water after the drying process and wet milling of the cellulose for 15 h. The size of NFC particles was around 300 nm, as evidenced by dynamic light scattering measurements ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…Nanofibrillated cellulose gel-like dispersion was prepared using mechanical treatment with a high shear force following the previously established method [ 51 ]. NFC fabrication is similar to MCC preparation but involves addition of water after the drying process and wet milling of the cellulose for 15 h. The size of NFC particles was around 300 nm, as evidenced by dynamic light scattering measurements ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…These results are similar to those obtained earlier with regard to a nanoparticle filler developed from bark. 10 In the latter case, the nanoparticle filler obtained from extracted black alder and pine bark, increased the tensile index in a dry state 1.40 and 1.30 times, the burst index 1.25 and 1.14 times, and the tensile index in a wet state 1.73 and 1.67 times, respectively, when used in the content of 20%.…”
Section: Results and Discussion Effect Of Nanocellulose Filler On Barmentioning
confidence: 89%
“…Our earlier works have shown that fillers and coatings obtained from nanoparticle gels produced from wood processing wastes considerably improve paper properties. [7][8][9][10] In this work, nanocellulose gels from fine fibre cellulose were obtained for their use in papermaking.…”
Section: Introductionmentioning
confidence: 99%